More than Copper : Toward the Diversification and Stabilization of Zambian Exports - Brulhart, Marius (World Bank Group, Washington, DC, 2015)
This paper analyzes Zambian export patterns using a new transaction-level trade data set for the period 1999-2011. The data show that, in international comparison, Zambian exports are exceptionally concentrated (on mining products). This reliance has been increasing in recent years. Zambia's exports are also characterized by a high level of churning of firms and products. Multivariate models of survival probabilities suggest that exchange rate volatility and difficult access to imported inputs significantly inhibit diversified and stable exports. The econometric analysis is complemented with a qualitative study of the Zambian export sector. The analysis concludes that one of the main policy levers for unleashing Zambia's full potential as an exporter is by facilitating access to imported inputs. Additional measures that ease foreign exchange transactions, simplify export and certification requirements, and increase the predictability of Zambia's trade regime could be effective to promote Zambia's nontraditional exports.